ACCREDITATION OF FORENSIC SCIENCE ORGANIZATIONS AND CERTIFICATION OF FORENSIC EXAMINERS IN LATVIA - M. Rēpele; M. Alksne; M. Čentoricka (Теория и практика судебной экспертизы, 2014)
The paper consists of two parts. The !rst describes the process of accreditation offorensic institutions in Latvia. References to standards, preparation for accreditationand validation of methods is also given in the article. The second part of the articlefocuses on the certi!cation of forensic experts in Latvia: describes the training programof candidates, the process of certi!cation and recerti!cation of experts, as well as thenational register of court experts.